The effectiveness of teamwork and its role in Strengthening the strategy of the Algerian foundation: A field study in the main unit of civil protection in laghouat - BOUMEDIAN, Zoulikha; AISSANI, Noureddine (Social Sciences Journal, 2021)
This research aims to highlight the role that effective work teams play in strengthening the strategy of the Algerian institution, and the study also included other objectives represented in revealing the scientific aspects of the study variables and understanding their dimensions, which contributes to enriching the scientific knowledge of officials and their ability to understand the reality of work in a scientific way. As they have practically understood, and to test the hypotheses of the study, we used the observation, questionnaire and interview tool, and we also relied on unpacking and processing statistical data by relying on the statistical packages for social sciences (SPSS version 21.0). The study ended with a set of findings and recommendations, the most important of which is that distinguished work teams play an important role in improving the organization’s strategy, and that not investing in effective teams results in weaknesses and threats to the organization.